PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS NIAS - RINCE ASTUTI ZEGA; MARIA MAGDALENA BATE’E; YAKIN NIAT TELAUMBANUA (LP2MTBM MAKARIOZ, 2022)
Financial problems will always be owned by every individual. Nowadays financial problems are the main issue in problems both in work matters and household affairs. These financial problems will also be closely related to the level of poverty in an area. Financial problems are closely related to financial management where it is hoped that good financial management will have an impact on the economic stability of each individual to overcome poverty for him. The development of the times and current technology actually has a positive impact on people's attitudes and behavior in managing their finances. The public will easily get financial management information through financial literacy. The purpose of this research was conducted to find out whether financial literacy influences the financial behavior of students of the Management Study Program, Faculty of Economics, and University of Nias. The researcher had 47 student respondents by taking the subject, namely 15% (Arikunto) of the total population of 314 class 2020 students in the Management Study Program, Faculty of Economics, and University of Nias.